EDUCATION SYSTEM OF THE UNITED STATES OF AMERICA - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
In this article, the American education system, which is considered advanced today coherence and continuity, educational stages are described in detail in sequence. It includes the main functions of pre-school education, secondary education and higher education revealed, in addition, about the volume and quality of hours allocated for classes data and conclusions are presented.